Circulating miRNAs: messengers on the move in cardiovascular disease - Egea, Virginia; Schober, Andreas; Weber, Christian (Thrombosis and Haemostasis, 2012)
Note: The review process for this paper was fully handled by G. Y. H. Lip, Editor in Chief.